Pengaruh Penyuluhan Kesehatan Tentang Metode Kontrasepsi Jangka Panjang (MKJP) Terhadap Pengetahuan Pasangan Usia Subur (PUS) Di Wilayah Kerja Puskesmas Sayur Matinggi Kecamatan Ujung Padang Kabupaten Simalungun Tahun 2022 - Ayu Jani Puspita Sari, Susilawati (Journal of Health and Medical Science, 2022)
WHO data in 2018 showed that the use of modern contraception slightly increased from 54% in 1990 to 57.49% in 2015. The achievement of active family planning participants in the District of Sayur Matinggi Health Center, Ujung Padang District has increased until 2016 (76.38%). and experienced a slight decline and had not yet reached the target in 2017 which was 76%. The Family Planning Program (KB) has been inaugurated nationally since 1970. However, population density in Indonesia remains a problem that has not been fully resolved until now. As a step to overcome population problems in Indonesia, BBKBN took action to promote family planning programs in the top ten provinces that account for the largest population in Indonesia. The purpose of this study was to determine the effect of health education on long-term contraceptive methods (MKJP) on knowledge of couples of childbearing age (EFA) in the work area of ??Sayur Matinggi Health Center, Ujung Padang District, Simalungun Regency in 2022. This type of research was quantitativel with a pre-post test design. of 122 Couples of Childbearing Age (EFA). Statistical analysis using paired sample T-test. The results of statistical tests obtained a value of 0.028 (p <0.05) so it can be concluded that there is a significant difference or influence between knowledge of EFA before and after being given counseling. The conclusion of this study is that there is an effect of health education on the level of knowledge of couples of childbearing age (EFA) in the use of long-term contraceptive methods. This can be seen through the change in the level of knowledge between before and after the provision of health education. These changes are in the form of increasing knowledge of couples of childbearing age about long-term contraceptive methods.